PERTUMBUHAN BIBIT HASIL OKULASI PADA BEBERAPA KLON JATI DARI GUNUNGKIDUL DAN WONOGIRI - Hamdan Adma Adinugraha; Abdul Aziz Efendi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Multiplication of teak clones can be conducted by using vegetative methods either macro or in vitro. In this research, several teak clones collected from Gunungkidul and Wonogiri were propagated using bud grafting technique to know the variation of their growth ability in the nursery. This research arranged in nested design, with 25 clones nested in 3 locations of scion source (clonal test at Gunungkidul, progeny test in Gunungkidul and clonal test in Wonogiri). Each treatment was repeated in 5 replications and each replication consisted of 10 bud grafted seedlings. The result showed that there were significant variations of growth among the clones in all observation characters, whereas the location of scion source was not significant. The best survival percentage of bud grafting from 3 sites of scion source were Clone 8 from the clonal test in Gunungkidul, Clone 64 from progeny test in Gunungkidul, Clone 43 and 87 from the clonal test in Wonogiri.